Effect of WS2 and Redmud reinforcements on mechanical behaviour of Al6061-T6 surface composite. (2021) - Kumar, M.; Senthilkumar, C.; Joel, E.; Vasanthaseelan, S.; Logeaswaran, M.
Abstract: Friction Stir Processing (FSP) is the most recent manufacturing technique that adopts the principle of Friction Stir Welding (FSW) to produce surface composites. FSP is a solid state processing technique that produces modified microstructures of composites. In this present work, Al6061-T6 alloy is selected as a base metal as it has improved physical and mechanical properties, and Redmud and WS2 are chosen as reinforcements. The aim of this paper is to investigate the effect of Redmud and WS2 reinforcements on FSPed Al6061 composites. Different wt% of reinforcements like 100% WS2, 100% Redmud and combination of 50% WS2 and 50% Redmud are added to the matrix to determine the tensile strength and hardness of FSPed surface composites. Experimental results revealed that all the reinforced surface composites recorded the reduced tensile strengths as compared to the Al6061-T6 base alloy. However, the combination of 50% WS2 and 50% Redmud reinforced surface composite exhibits higher hardness than the other two surface composites.